Case Report: Anomalous Experience in a Dissociative Identity and Borderline Personality Disorder - Martins, Hugo André de Lima; Ribas, Valdenilson Ribeiro; dos Santos Ribas, Ketlin Helenise; da Fonseca Lins, Luciano; Mainieri, Alessandra Ghinato (Frontiers in Psychiatry, 2022)
Introduction Dissociative identity disorder, formerly called multiple personality disorder, is a rupture of identity characterized by the presence of two or more distinct personality states, described in some cultures as an experience of possession. Objective The case of a 30-year-old woman with dissociative identity disorder and borderline personality disorder associated with a previous history of anomalous experience was reported. Case Report A 30-year-old woman who fulfilled the DSM-5 criteria for dissociative identity disorder and borderline personality disorder reported the presence of unusual sensory experiences (clairvoyance, premonitory dreams, clairaudience) since she was 5 years old. The patient told that for 12 months she presented episodes in which a “second self” took charge of her actions: she would then speak with a male voice, become aggressive, and require several people to contain her desire for destruction. After 3 months of religious follow-up, and accepting her unusual experiences and trance possessions as normal and natural, she had significant improvement. Conclusion When approaching DID and BPD patients, it is necessary to observe the anomalous phenomena (in the light of) closer to their cultural and religious contexts, to promote better results in the treatment of their disorders, which has not been explored in the treatment guide.